Functional state of the kidneys in children who suffered acute kidney injury in the catamnesis of observation - Lavrenchuk, O.V.; Bagdasarova, I.V.; Ponomareva, M. A. (Ukrainian Journal of Nephrology and Dialysis, 2018)
Acute kidney injury (AKI) in children has a polyethiological structure, peculiarities of the course of age-related diseases and a high risk of developing chronic kidney disease (CKD) in catamnesis. The aim of the study was to study the functional status of the kidneys in children undergoing AKI in remote terms. Materials and methods. The functional status of the kidneys (velocity of the balloon filtration (GFR) by Schwartz, the level of parathyroid hormone (PTH), albuminuria (AU), dynamic and static renoscintigraphy (RSG)) were analyzed retrospectively, according to 60 histories of diseases of children aged 1 to 18 years old AKI during 2000-2016. Results. During the first year of follow-up, 61.5% of patients retained blood azotemia, slowed GFR, and high AU. Further follow-up of this group of patients revealed a tendency to normalize the levels of creatinine, urea, and GFR, but the increase in AU levels. In the follow-up dynamics of 5 to 15 years, it was determined that in 13.3% of patients, GFR ranged from 90 to 85 ml / min, and in 36.7% - from 85 to 30 ml / min. In 46.7% of children with unchanged creatinine and GFR, an increase in albuminuria from 45 to 601 mg / day was noted. During the observation period, 15 years or more, 53.3% of the child was fully recovered; in 31.6% of patients, chronic renal failure (CRF) was diagnosed, and 30.0% had a defective recovery - a consistent reduction of the function with available markers of damage kidney. Conclusions. Acute kidney damage was more common among children of the first 3 years of life, mainly in boys. The etiological factor of the onset of the disease was hemolytic uremic syndrome on the background of acute intestinal infection. A complete recovery was documented in 20.0% of the reconvalescents of the AKI, in 30.0%, the persistence of renal damage markers with function restoration was confirmed, and in 18.3% a significant, steady decline in the function of the kidneys. A multi-purpose scintigraphic study with radiopharmaceuticals with different drags showed signs of tubal and glomerular disorders in 7-8 years before laboratory changes.